2018
DOI: 10.1177/0272431618798514
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Upstanding Behavior in Youth: A Proposed Model

Abstract: Despite what we have learned about the causes and consequences of bullying, efforts to reduce bullying through interventions to date have yielded modest results. Most bullying prevention efforts have targeted perpetrators and victims, ignoring the powerful role that observers play in maintaining cycles of bullying. This article presents literature from the fields of bystander behavior, empathy training, multicultural education, and ally/social justice orientation development; integrates relevant findings; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The challenge is that those adults are often viewed as being in positions of power and are the ones who bring disciplinary sanctions or other unwanted consequences (such as confiscating devices or prohibiting social media use) (Madden et al, 2012). This also points to an area where greater education (e.g., through role-playing, modeling, social justice storytelling, empathy training, and clear direction to students and families) can make a difference (Finkelhor et al, 2014;Vera et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…The challenge is that those adults are often viewed as being in positions of power and are the ones who bring disciplinary sanctions or other unwanted consequences (such as confiscating devices or prohibiting social media use) (Madden et al, 2012). This also points to an area where greater education (e.g., through role-playing, modeling, social justice storytelling, empathy training, and clear direction to students and families) can make a difference (Finkelhor et al, 2014;Vera et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…To advance the conceptualization of bystanders and their decision-making from BIM, we proposed the upstanding for promotion-prevention (UPP) model. The UPP model stands atop a rich theoretical foundation of promotion and prevention science (Catalano et al, 2002;Kia-Keating et al, 2011), regulatory focus and fit theories from motivation science (Higgins, 1997;Scholer et al, 2019), reinforcement theory from applied behavioral science (Biglan, 2003;Biglan et al, 2012;Geller, 2001;McCarty et al, 2021), and previous bystander intervention research encouraging various forms of prevention upstanding (e.g., Banyard et al, 2019Banyard et al, , 2021Hamby et al, 2016;Hart & Miethe, 2008;Moschella & Banyard, 2020;Vera et al, 2019). Additionally, the UPP model answers prior calls by researchers to address multiple risks and forms of harm, while also broadening efforts to attend to multiple assets and forms of benefit (i.e., extending across prevention/promotion opportunities and health-depreciating and health-promoting settings; Hamby & Grych, 2013;McMahon et al, 2022;McMahon & Banyard, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, research studies on bystander behaviors focus on the elements and interplay of situational (e.g., possible costs to the self), interpersonal (e.g., relationship with others involved), and dispositional factors (e.g., motivation, personality traits, self-efficacy, victimization history) that influence bystander behavior (e.g., Mainwaring et al, 2022;Vera et al, 2019;Woods et al, 2020). For example, studies have found U.S. students are more likely to endorse or be observed upstanding when they are at lower risk of personal costs or setbacks (Spadafora et al, 2020), when there are fewer perceived barriers to intervention (e.g., friends arguing not to become involved; Bennett et al, 2014), and when they have more social capital and perceived support (Evans & Smokowski, 2015).…”
Section: Bystander Behaviormentioning
confidence: 99%
“…Supporting or defending targeted peers is often referred to in research on bullying and cyberbullying as “upstanding” (Casey, Lindhorst, & Storer, 2017; Vera et al, 2018). There has been little focus on how to promote upstanding in response to bullying or cyberbullying among college students, but among children and adolescents it is associated with higher rates of empathy, stronger antibullying feelings, and past experiences of being bullied or upstanding (Vera et al, 2018). Situational factors and group norms may be at least as predictive, however (Barhight, Hubbard, Grassetti, & Morrow, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%